PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN CONVENIENCE GOODS PADA KONSUMEN SWALAYAN KUD PAKIS - Muhammad Rukmana; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to find out and analyze the effect of simultaneous and partial variables on product quality, service quality, price and word of mouth promotion on goods purchasing decisions in KUD Pakis supermarket customers. With this type of research is explanatory, namely research explains. This research was conducted in April-July 2019, and took place at KUD Pakis supermarket, Pakis District, Malang Regency. The population in this study amounted to 1,750 obtained in April 2019, and the sample used the accidental sampling method with 95 respondents. This study uses primary data through questionnaires and measurement scale is a Likert scale. The analytical tool in this study uses the Test Instrument data method, Normality test, multiple regression analysis, and Classical Assumption Test.Based on the results of the statistical test, the results show that product quality, service quality, price and word of mouth simultaneously influence purchasing decisions. And partially product quality, service quality and price have a positive and significant influence on purchasing decisions, while word of mouth has no significant effect on purchasing decisions.Keywords: Product Quality, Service Quality, Price, Word Of Mouth, Purchase Decision